MYCN Function in Neuroblastoma Development - Otte, Jörg; Dyberg, Cecilia; Pepich, Adena; Johnsen, John Inge (Frontiers in Oncology, 2021)
Dysregulated expression of the transcription factor MYCN is frequently detected in nervous system tumors such as childhood neuroblastoma. Here, gene amplification of MYCN is a single oncogenic driver inducing neoplastic transformation in neural crest-derived cells. Being one of the strongest predictors of poor prognosis, abnormal MYCN expression is usually present at diagnosis but is never acquired during later tumorigenesis in MYCN non-amplified neuroblastoma. This suggests that increased MYCN expression is an early event in these cancers leading to a peculiar dysregulation of cells resulting in embryonal or cancer stem-like qualities such as an increased self-renewal, apoptotic resistance or metabolic flexibility.